Perkembangan Syair Janturan Jejer Pertama pada Pakeliran Wayang Kulit Gaya Surakarta - Timbul Subagya (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
Wayang kulit is a Javanese culture that is still developing in the midst of the rapid development of information technology. The longlife existence of wayang shows that until now it is still an idol for its community, even there have been changes and developments from its conventional form. This article examines the changes and catur in wayang kulit performance, especially the janturan, the first scene in wayang kulit repertoire of some dalang that exist today. The results show that the development of janturan is still impersonal, the changes made by a few dalang are still individual.Keywords: development, poetry Janturan, wayang performance